The Role of Communication in Shaping Public Perception of Carbon Capture, Utilization, and Storage (CCUS) Development - Pradhipto Bagas Wicaksono; Purnaning Tuwuh Triwigati; Muhamad Hidayat (Institut Komunikasi dan Bisnis LSPR, 2026)
Carbon Capture, Utilization, and Storage (CCUS) technologies represent a pivotal technological advancement to mitigate the climate crisis by capturing and repurposing carbon dioxide (CO2) emissions. However, their viability is often questioned, with opposition rooted in skepticism about safety, effectiveness, and environmental risks. This study examines these perspectives alongside the development, research efforts, and milestones achieved by CCUS technologies for reducing greenhouse gas emissions. By analyzing media representations and activist perspectives, this study aims to provide a comprehensive overview of how CCUS is framed in public discourse and to propose effective communication strategies that can foster a more informed and supportive attitude. The results underline the importance of engaging local communities through educational initiatives and partnerships with trusted stakeholders particularly organizations to demystify CCUS technologies. Public perception remains a critical factor, as misrepresentations and fear perpetuated by media and advocacy groups hinder broader acceptance. The opposition is primarily driven by narratives that frame CCUS as a costly, ineffective, and risky technology that serves to prolong the fossil fuel industry. A shift in the narrative surrounding CCUS is needed, emphasizing its role in economic opportunities and sustainability, which is very crucial for the successful implementation in Indonesia and beyond.